Serum Cytokine Profiles As Biomarker In Multi-Drug Resistant Tuberculosis (MDR-TB). - Boakye, A.N. (University Of Ghana, 2017)
Background: Tuberculosis (TB) remains a major threat to public health despite several efforts to curb the disease. Contributions made by TB control programs have been tremendous; however, the emergence of multi-drug resistant (MDR) tuberculosis is a big threat to the control efforts and calls for innovative measures to mitigate the effect. New TB control programs with a comprehensive approach to dealing with MDR-TB is needed globally. In particular, new non-sputum based diagnostic tools capable of monitoring treatment response would be novel in this regard. The immune system with its associated cytokines plays a pivotal role in host response to Mycobacterium tuberculosis infection. The dynamics of cytokines at different stages of infection may therefore be useful as diagnostic biomarkers that could also be useful in monitoring response to TB treatment as well as in phase II clinical trials. Aim: To evaluate the levels of eight cytokines in the serum of drug susceptible and MDR-TB patients and determine the utility of a single or multiple cytokine profile as a surrogate biomarker for MDR-TB. Methodology: The study was cross-sectional using sixty-four archived serum samples of MDR (n=21), active TB patients (n=25) and healthy controls (n=18). Healthy controls were individuals who were not infected with TB (Quantiferon TB test negative). Serum levels of TNF-α, IFN-γ, IL-17A, IL-6, IL-10, Granzyme B, IL-4 & IL-12 p70 in each group was quantified by multiplexing using the Luminex™ 200 system. Data was entered into Microsoft Excel V10. Further analysis was performed using GraphPad Prism Version 7.03 and SPSS Version 23. Statistical significance underthe Graph Prism and Analysis of Variance (ANOVA) was used toassess the ability of each cytokine(s) to discriminate between different population groups. Mann-Whitney test was used to analyze concentration differences of each of the eight cytokines between the groups. The relationship between two cytokines was assessed using Spearman correlation analysis (rho value). The sensitivity and specificity of the variables were analyzed using ROC curves. Differences between groups were considered significant at p–values less than 0.05. Results: Serum levels of IFN-γ, IL-4 and TNF-α were significantly elevated in TB and MDR-TB cases compared to healthy controls (p=0.01, p=0.0001, p=0.0001 respectively). In addition to IFN-γ, IL-4 and TNF-α, serum levels of IL-6, IL-10 showed significantly higher levels in only TB cases compared to healthy controls (p=0.0001, p=0,01, p=0.00001, p=0.001, p=0.01 respectively). However, the serum cytokine concentrations of MDR-TB cases compared to their active TB counterparts showed no significant difference. Additionally, the diagnostic potentials of IL-4, TNF-α, Granz B, IL-10, IL-6and IFN-γ showed a trend of higher sensitivity between MDR-TB/TB and No TB cases. The sensitivity patterns IL-4, TNF-α, and Granzyme B were significant among all the population groups (p=0.009, p=0.003, p=0.009 respectively). Conclusion: The results point to dysregulated serum cytokine profile in patients with MDR-TB similar to that observed in active TB cases. The study identified unique cytokine patterns characteristic of MDR-TB, TB and No TB subjects. Estimation of the serum levels of IFN-γ, IL-4, IL-6, IL-10 and TNF-α may be useful as biomarkers for distinguishing MDR-TB or TB cases from healthy individuals and thus may contribute to TB management and monitoring treatment responses.
MSc.
Keywords: Multi-Drug Resistant Tuberculosis (MDR-TB); Serum Cytokine